2022
DOI: 10.7150/jca.65687
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 mediates Cetuximab resistance in Colorectal Cancer via the MiR-495 and HGF/c-MET Pathways

Abstract: Background: Cetuximab is one of the most widely used monoclonal antibodies to treat patients with RAS/BRAF wild-type metastatic colorectal cancer (mCRC). Unfortunately, cetuximab resistance often occurs during targeted therapy. However, the underlying epigenetic mechanisms remain unclear. Our previous study demonstrated that the exosomal transfer of urothelial carcinoma-associated 1 (UCA1) confers cetuximab resistance to CRC cells. The goal of this study was to elucidate the detailed role of UCA1 in cetuximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…A recent study revealed that UCA1 enhances cetuximab resistance by targeting miR‐495 and suppressing its expression in CRC 49 . Through the use of five miRNA target identification algorithms, it was determined that hepatocyte growth factor (HGF) and c‐mesenchymal‐to‐epithelial transition (c‐MET) were targets of miR‐495 49 . c‐MET, a tyrosine kinase receptor for HGF, is notable for its capacity to induce cancer 51 .…”
Section: Lncrna/mirna/mrna Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that UCA1 enhances cetuximab resistance by targeting miR‐495 and suppressing its expression in CRC 49 . Through the use of five miRNA target identification algorithms, it was determined that hepatocyte growth factor (HGF) and c‐mesenchymal‐to‐epithelial transition (c‐MET) were targets of miR‐495 49 . c‐MET, a tyrosine kinase receptor for HGF, is notable for its capacity to induce cancer 51 .…”
Section: Lncrna/mirna/mrna Networkmentioning
confidence: 99%
“…c‐MET, a tyrosine kinase receptor for HGF, is notable for its capacity to induce cancer 51 . Moreover, HGF was found to reduce the cetuximab‐induced suppression of cell growth in CRC cells by activating the HGF/c‐MET axis 49 . The HGF/c‐MET axis has emerged as a potential therapeutic target for a variety of malignancies, including CRC, as indicated by a growing body of research 52 .…”
Section: Lncrna/mirna/mrna Networkmentioning
confidence: 99%
“…A large number of lncRNAs have also been shown to induce drug resistance in cancer cells [62][63][64]. Overexpression of UCA1 has been reported to be associated with resistance to chemo-therapeutic drugs, including 5-fluorouracil, cisplatin, gemcitabine, paclitaxel, docetaxel, gefitinib, cetuximab, doxorubicin, daunorubicin, tamoxifen, temozolomide, and trastuzumab, in many kinds of tumor cells [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Recently, the role of UCA1 in the chemoresistance of PaC has also been investigated.…”
Section: Uca1 Increases Drug Resistance In Pacmentioning
confidence: 99%
“…UCA1 acts as a ceRNA to regulate the target genes expression at the post-transcriptional level [149][150][151], and it is overexpressed in CRC cells and tissues. As a sponge for miR-495, UCA1 binds and inhibits miR-495, promotes the expression of hepatocyte growth factor (HGF) and c-MET, activates the HGF/c-MET signaling pathway in CRC cells, and attenuates the Cetuximabinduced cell proliferation inhibition, thereby promoting Cetuximab resistance [32].…”
Section: Upregulated Lncrnasmentioning
confidence: 99%
“…In addition to lncRNAs and circRNAs, ceRNAs include endogenously transcribed pseudogenes [ 29 , 31 ]. In recent years, ceRNAs have been found to be involved in tumor development, and ceRNA networks play an important role in resistance to anti-EGFR mAbs in CRC [ 30 , 32 , 33 ]. This paper mainly reviewed the lncRNAs, miRNAs, and circRNAs related to anti-EGFR mAbs resistance, and elucidated their correlation with anti-EGFR mAbs resistance for CRC and the potential mechanism, providing new methods and ideas for predicting the prognosis and treatment of CRC patients.…”
Section: Introductionmentioning
confidence: 99%